Lower Coverdale and Gaytons: Middle Devonian and possibly older anorthosite-ferronorite, gabbro, and quartz monzonite intrusions in southeastern New Brunswick - Barr, Sandra M.; White, Chris E.; Hamilton, Mike A. (Atlantic Geoscience, 2007)
The Lower Coverdale intrusion near Moncton, New Brunswick, has been intersected in drill holes at depths of 100–200 m below unconformably overlying Carboniferous sandstone, onglomerate and, locally, limestone of the Windsor, Mabou, and Cumberland groups. A large positive aeromagnetic anomaly suggests that the intrusion has a subsurface area of at least 30–40 km2. As revealed by drill core and cuttings, the intrusion consists of interlayered coarse-grained anorthosite and ferronorite, both intruded by gabbro, quartz monzonite, and minor felsic dykes. The ferronorite is high in Ti and P, and contains interstitial patite and ilmenite/magnetite and layers of apatite-ilmenite rock (nelsonite) up to several metres thick. Much of the core shows pervasive effects of metamorphism and alteration but microprobe analyses of the freshest samples revealed that the plagioclase in both anorthosite and ferronorite has andesine composition. The anorthosite and ferronorite are chemically distinct, but their close spatial association suggests a genetic link. In contrast, the younger gabbroic rocks differ in mineralogy and chemistry from, and appear unrelated to, the anorthosite and ferronorite. They are altered but not metamorphosed, and preserve intergranular textures. They contain more calcic plagioclase and augite, and have low Ti and P. The deepest drill hole in the Lower Coverdale intrusion encountered highly altered coarse-grained quartz monzonite at a depth of 1095–1206 m. The quartz monzonite is mineralogically and chemically similar to quartz monzonite in quarries near Gaytons, 20 km to the east. Virtually identical Middle Devonian U-Pb zircon ages of 90.6 ± 1.0 Ma and 390.0 ± 0.5 Ma were obtained for samples from the Lower Coverdale and Gaytons quartz monzonite, espectively. However, the anorthosite-ferronoritegabbro is likely considerably older: perhaps ca. 540 Ma like gabbroic rocks elsewhere in the Brookville terrane; or possibly esoproterozoic, like intrusions with similar characteristics in Grenvillian parts of the Precambrian shield. RÉSUMÉ On a croisé l’intrusion de Lower Coverdale près de Moncton (Nouveau-Brunswick) dans des puits forés à des profondeurs de 100 à 200 m au-dessous de grès du Carbonifère sus-jacent non concordant, de conglomérat et, par endroits, de calcaire des groupes de Windsor, de Mabou et de Cumberland. Une anomalie aéromagnétique positive étendue permet de supposer que l’intrusion a une superficie souterraine d’au moins 30 à 40 kilomètres carrés. Les carottes de forage et les déblais révèlent que l’intrusion est constituée de ferronorite et d’anorthosite à grains grossiers interstratifiées, toutes deux pénétrées par du gabbro, de l’adamellite et des dykes felsiques secondaires. La ferronorite est riche en Ti et en P et renferme de ’ilménite/magnétite et de l’apatite interstitielles ainsi que des couches d’ilménite-apatite (nelsonite) pouvant avoir plusieurs mètres d’épaisseur. Une vaste part des carottes témoignent des effets intenses d’un métamorphisme et d’une altération, mais des analyses à la microsonde des échantillons les plus frais ont révélé que le plagioclase à l’intérieur de l’anorthosite et de la ferronorite est composé d’andésine. L’anorthosite et la ferronorite sont chimiquement distinctes, mais leur association spatiale étroite laisse supposer un lien génétique. Par contre, les roches gabbroïques plus récentes ont une composition minéralogique et chimique différant de celles de l’anorthosite et de la ferronorite et elles ne semblent pas y être apparentées. Elles sont altérées mais ne sont pas métamorphisées et elles conservent des textures intergranulaires. Elles renferment plus de plagioclase calcique et d’augite et ont une faible teneur en Ti et en P. Le puits de forage le plus profond dans l’intrusion de Lower Coverdale a recoupé de l’adamellite à grains grossiers fortement altérée à une profondeur de 1 095 à 1 206 m. L’adamellite est minéralogiquement et chimiquement similaire à l’adamellite des carrières situées près de Gaytons, à 20 kilomètres à l’est. On a obtenu des datations U-Pb sur zircon pratiquement identiques du Dévonien moyen de 390,6 ± 1,0 Ma et de 390,0 ± 0,5 Ma d’échantillons d’adamellite de Lower Coverdale et de Gaytons, respectivement. Le gabbro l’anorthosite-ferronorite, toutefois, est probablement beaucoup plus âgé : il a peut-être 540 Ma, comme les roches gabbroïques d’ailleurs à l’intérieur du terrane de Brookville, ou il pourrait remonter au Mésoprotérozoïque, comme les intrusions présentant des caractéristiques analogues dans les parties grenvilliennes du bouclier précambrien.